Virtual Reality for Medical Training - Andrade, José Raul B.; Araújo, Antonio C. V.; Moraes, Ronei M.; Machado, Liliane S. (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR); 2024: Anais Estendidos do XXVI Simpósio de Realidade Virtual e AumentadaDO - 10.5753/svr_estendido.2024.244697, 2024)
The goal of this demonstration is to present an immersive virtual reality environment aimed at training healthcare procedures. The environment was developed to be immersive and interactive and can be executed with the Meta Quest device.